Lingual Pustular Psoriasis and Acrodermatitis Continua of Hallopeau Successfully Treated with Adalimumab: A Rare Case Report and Review of Oral Psoriasis - Sarah J.J. Touyz; Melanie Pratt (European Medical Journal, 2018)
Psoriasis is a common skin disease with various cutaneous manifestations and is classified into two clinical groups: non-pustular and pustular. Pustular psoriasis is less common than non-pustular forms of psoriasis and is particularly resistant to treatment. Studies of the rarer variants of acrodermatitis continua of Hallopeau and pustular psoriasis of the tongue remain scant. The subtypes of psoriasis can present all over the body, including in uncommon locations, such as the oral cavity; however, there are limited presentations and data regarding oral involvement in psoriasis and its subsequent management. Although cases involving oral psoriasis are rare, with <100 publications in the literature, and generally asymptomatic, recent studies have suggested that it is more prevalent than once thought. In contrast, presentation and subsequent management of lingual pustular psoriasis have not been reported. Presented and discussed in this review is a rare case of symptomatic, painful lingual pustular psoriasis and acrodermatitis continua of Hallopeau with complete remission after the use of adalimumab, followed by a thorough review of the histopathology, diagnosis, and clinical management of oral psoriasis. The use of biologics for conditions involving the oral mucosa, particularly in the setting of cutaneous psoriasis, is a novel concept with potential application in the fields of dermatology, oral medicine, and rheumatology.